Digital solutions transform the forest-based bioeconomy into a digital platform industry - A suggestion for a disruptive business model in the digital economy. (August 2018) - Watanabe, Chihiro; Naveed, Nasir; Neittaanmäki, Pekka
Abstract: With the notion that the transformation of the forest-based bioeconomy in recent years provides insightful suggestions not only on the bioeconomy, but on business innovation, this paper conducts an empirical analysis of the transformation and attempts to extract suggestions for a digital-solution-driven, disruptive business model in the digital economy. Notwithstanding the potential broad cross-sectoral benefits, the natural environment, locality constraints, and incessant challenge of distance have impeded the balanced development of the bioeconomy. However, driven by digital solutions, the bioeconomy has taken big steps forward in recent years. Digitalization has enabled real-time, end-to-end supply chain visibility, improved delivery accuracy as well as stock level optimization and alignment with demand planning. The advancement of e-commerce has also led to the elimination of distance between both the upstream and the downstream of the chain. This paper demonstrates a transformative stream observed at the forefront of the forest-based bioeconomy chain. An empirical analysis focusing on the core business activities at the forefront, both upstream and downstream of the chain, is conducted. A new insight common to all industries in the digital economy is thus explored for constructing a creative disruption platform by embracing digital solutions. Highlights: Digital solutions transforming the forest-based bioeconomy into a digital platform industry were analyzed. Suggestions for a digital solution-driven disruptive business model were extracted. Transforming stream observed at the forefront of the forest-based bioeconomy chain was demonstrated. An empirical analysis on the noteworthy business activities at upstream and downstream was attempted. Amazon's business model was analyzed.